p63 expression in normal skin and usual cutaneous carcinomas. - Reis-Filho, J (2002)
BACKGROUND: p63 is a p53 homologue that is mapped to chromosome 3q27. This gene encodes six different isoforms, which have either transactivating or dominant negative effects on p53-reporter genes. It has been described that in contrast to p53, p63 seems not to be associated with tumor predisposition, as neither p63 knockout mouse models nor germline p63 mutations are related to an increased risk of tumorigenesis. It has been demonstrated that p63 is a reliable keratinocyte stem cell marker and that it is involved in the maintenance of the stem cell population. Scant data on p63 expression in normal skin, basal cell carcinomas (BCCs), keratoacanthomas and squamous cell carcinomas (SCCs) have been reported. We herein evaluated p63 expression in 16 BCCs, one keratoacanthoma and 13 SCCs. METHODS: Immunohistochemistry according to the streptavidin-biotin-peroxidase technique, using the antibody 4A4 raised against all p63 isoforms, was performed. p63 expression was evaluated in epidermal cells and skin appendages. Semi-quantitative evaluation (-, +, ++, +++) of p63 expression in BCCs, keratoacanthoma and SCCs was carried out. Only nuclear expression was considered as specific. RESULTS: p63 was expressed in the nuclei of epidermal basal and suprabasal cells, in the cells of the germinative hair matrix and the external root sheath of hair follicles, in the basal cells of the sebaceous gland and in the myoepithelial/basal cells of the sweat glands. All terminally differentiated cells were negative for p63. All BCCs showed ++ to +++ immunoreactivity. At variance, keratoacanthomas and grade I and II SCCs showed variable p63 reactivity in a basal layer-like distribution, whereas undifferentiated cells of grade III SCCs showed ++ to +++ positivity. A grade IV spindle SCC showed + immunoreactivity. The SCCs in situ showed remarkable expression of p63 in all cell layers. Terminally differentiated squamous cells were either negative or showed only focal immunoreactivity in the carcinomas. CONCLUSIONS: p63 is consistently expressed in the basal cells of epidermis and cutaneous appendages, including the basal/myoepithelial cells of sweat glands. Based on our findings, the balance of probabilities favors that p63 might play a role in the pattern of differentiation and in the oncogenesis of usual carcinomas of the skin.